MANAGEMENT OF OCHRATOXIGENIC FUNGI BY PHYTOCHEMICALS OF AMARANTHUS VIRIDIS L. - Z. Naeem; K. Jabeen1 and S. Iqbal (Journal of Animal and Plant Sciences, 2022)
Ochratoxigenic fungal species are a major cause of various infections in plants and posed serious threat to their consumers, including humans and animals. The objective of this study was to examine the in vitro efficacy of different concentrations of leaves methanolic extract of Amaranthus viridis L. against target pathogenic ochratoxin producing fungal species (Trichoderma viride Pers., Trichoderma harzianum Rifai. and Cladosporium cladosporioides(Fresen.) G.A. de Vries). For this purpose, different concentrations viz. 2%, 4%, 6%, 8% and 10% of leaf methanolic extract was prepared and tested for its antifungal potential in a completely randomized design (CRD). Results revealed that a 10% concentration of A. viridis significantly suppressed the growth of all the tested fungi. The phytochemical analysis of A. viridis depicts the presence of glycosides, alkaloids, saponins, tannins and coumarins. Bioassay-guided fractionation was executed to check the antifungal activity of various fractions in vitro against the test ochratoxin producing fungi. The ethyl acetate fraction showed the highest antifungal activity among all other fractions. GC-MS (Gas chromatography-mass spectroscopy) analysis of ethyl acetate fraction revealed the presence of twelve compounds viz. 1,2,3-propanetriol monoacetate; n-decanoic acid; 1-hexadecene; dodecanoic acid; 5,6,7,7a-tetrahydro-4,4,7a-trimethyl-[R]; tetradecanoic acid, 2-pentadecanone; 6,10,14-trimethyl-; phenol,2- methyl-5-[1-methylethyl]-; n-hxadecanoic acid; 2[4H]-benzofuranone; phytol; 9,12- octadecadienoic acid and heptacosane. The presence of these compounds might be responsible for the antifungal potential of A. viridis and it can be concluded that the methanolic leaf extract of the tested plant proved to be beneficial for inhibiting the growth of test ochratoxigenic fungi.
Keywords: Bioassay; GC-MS; ochratoxin; phytochemicals